2020
DOI: 10.35728/jmkik.v5i1.123
|View full text |Cite
|
Sign up to set email alerts
|

Pendidikan Kesehatan (Personal Hygiene) Terhadap Tingkat Pengetahuan, Sikap Dan Tindakan Personal Hygiene Anak Usia Sekolah

Abstract: Anak usia sekolah rentan terhadap infeksi yang timbul akibat kurangnya pemahaman dan respon maupun tindakan tentang personal hygiene. Masalah kesehatan yang sering muncul akibat tidak menjaga personal hygiene berupa karies gigi, kutu rambut, cacingan, diare, bahkan gangguan psikologis, sebagaimana yang terjadi pada siswa sekolah dasar negeri 016 Samarinda Ulu yang kurang memperhatikan personal hygiene baik kebersihan kulit rambut, kuku tangan dan kaki, kulit, pakaian, gigi dan mulut. Untuk mengetahui perbedaan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The results of this study are in line with a study conducted by Widyadhana et al (2022) SDN Pekarungan, Sukodono sub-district, Sidoarjo district, which showed that the singing method influenced increasing independence in personal hygiene carried out by school-age children (𝜌 = 0.000). The findings of this study support Mukaromah & Katharina's (2020) assumption that health promotion can influence behavior change, especially regarding personal hygiene practices. Singing will also allow the right brain to work more effectively, which will help children retain information for a more extended period after it has been presented to them.…”
Section: The Effect Of the Singing Methods On Independence In Persona...supporting
confidence: 83%
See 1 more Smart Citation
“…The results of this study are in line with a study conducted by Widyadhana et al (2022) SDN Pekarungan, Sukodono sub-district, Sidoarjo district, which showed that the singing method influenced increasing independence in personal hygiene carried out by school-age children (𝜌 = 0.000). The findings of this study support Mukaromah & Katharina's (2020) assumption that health promotion can influence behavior change, especially regarding personal hygiene practices. Singing will also allow the right brain to work more effectively, which will help children retain information for a more extended period after it has been presented to them.…”
Section: The Effect Of the Singing Methods On Independence In Persona...supporting
confidence: 83%
“…This study's results are lower than those of a study conducted by Aminingsih & Warsini ( 2021), which can be concluded if all respondents (100%) are at a less independent level. Likewise, in research (Mukaromah & Katharina, 2020) at SDN 016 Samarinda Ulu, which can be concluded if more than half of the respondents (54.5%) have a relatively independent level of independence, the research was carried out before being given personal hygiene health education using the singing method.…”
Section: Description Of Personal Hygiene Independence In School-age C...mentioning
confidence: 99%